Transdisciplinarity and Pedagogy: Notes for the Debate of the Un(Discipline) of the Pedagogue - Valladares, Liliana (2020)
This essay wonders about the transdisciplinary nature of pedagogy and its relation to the “hybrid” identity of the pedagogue. Different theoretical approaches to multi, inter and transdisciplinarity in the study of education are reviewed and the discussion about the epistemological status of pedagogy is synthetically recovered. It is discussed whether it is possible to understand education and the work of the pedagogue today from a unidisciplinary perspective; if pedagogy can be considered transdisciplinary, and if the hybrid identity of the pedagogue is an expression of the transdisciplinary character of the study of education.